Developments And Enlargement Of Women In The Society (International Journal of Food and Nutritional Sciences, 2022)
The decade after independence of India has seen tremendous historical changes in the status of women in Indian society. Since 1950’s, academicians have concentrated more on Women’s Studies, and different studies by different disciplines have given to it a new interpretation. The principle of gender equality is enshrined in the India Constitution. However, the government sponsored development activities have benefited only a small section of women, and women are facing gender discrimination in many fields. Women entrepreneurship must be moulded properly with entrepreneurial traits and skills to meet the changes and trends; it should challenge global markets and also be competitor enough to sustain and strive for excellence in the entrepreneurial area. The year 2001 was celebrated as women’s empowerment year. During this year various activities and programmes were taken up on different themes pertaining to women’s social, political and economic empowerment.